Effect Of Part Features On Dimensional Accuracy Of FDM Model - Mohd Nizam, Sudin; Shamsul Anuar, Shamsudin; Mohd Azman, Abdullah (Asian Research Publishing Network (ARPN), 2016)
This research investigates the dimensional accuracy of parts produced using the additive manufacturing method of Fused Deposition Modelling (FDM). The fabrication of parts was carried out based on the standard value of process parameter of Stratasys FDM 400MC machine. Parts with four common features of products in different sizes were fabricated in FDM machines using Acrylonitrile Butadiene Styrene (ABS) material. Then, the linear dimension of each part feature was measured with a Coordinate Measurement Machine (CMM) that was repeated for three times. The accuracy of the fabricated part feature was computed by subtracting the nominal dimension of the part (CAD model)with the measured dimension of FDM model. An analysis of sixteen different dimensions of the part feature was identified that parts dimension had a significant effect on the dimensional accuracy of FDM model. In addition, it was found that FDM machine is less accurate in producing a circular shape part such as cylindrical, sphere and hole as the majority of them are out of the machine’s tolerance.